Output planning at the input stage in visual working memory - Boettcher, SEP; Gresch, D; Nobre, AC; van Ede, F (American Association for the Advancement of Science, 2021)
Working memory serves as the buffer between past sensations and future behavior, making it vital to understand not only how we encode and retain sensory information in memory but also how we plan for its upcoming use. We ask when prospective action goals emerge alongside the encoding and retention of visual information in working memory. We show that prospective action plans do not emerge gradually during memory delays but are brought into memory early, in tandem with sensory encoding. This action encoding (i) precedes a second stage of action preparation that adapts to the time of expected memory utilization, (ii) occurs even ahead of an intervening motor task, and (iii) predicts visual memory–guided behavior several seconds later. By bringing prospective action plans into working memory at an early stage, the brain creates a dual (visual-motor) memory code that can make memories more effective and robust for serving ensuing behavior.